Correlation of modal parameters of a telecommunication tower using stochastic subspace identification algorithm and finite element modal analyis - Pe, Adolfo A.; Mata, William L.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Modal identification has been used in various engineering applications such as structural health monitoring, finite element model updating, structural damage detection, etc. Telecommunication towers are vital for communication but are very vulnerable to strong winds that is why there is a great need in determining the real dynamic characteristics of these structures. In this study, the modal parameters of a telecommunication tower will be identified to determine its dynamic characteristics using stochastic subspace identification (SSl) and finite element modal analysis. A program using Laboratory Virtual Instrument Engineering Workbench (Lab VIEW) will synchronize the field vibration measurements of 31 accelerometers. Results showed that the SAP frequency of2.2176 Hz agreed with the SSI frequency of 2.2508 Hz with a modal assurance criterion value of 0.8145 and a percent difference of 1.486%. The SAP frequency equal to 2.2720 Hz agreed with the SSI frequency of2.2586 Hz with a percent difference of 0.5915%. Damping factor values of 4.0288% and 1.0554% were obtained for the 2.2586 Hz and 2.2508 Hz frequencies, respectively.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Modal analysis; Radio and television towers -- Vibration